(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study is dedicated to examining partonymy in the Uzbek language, analyzing its structure and functions. The work explores the main types of partonymic relations, their role in the systemic organization of the lexicon, and their impact on the formation and clarification of word meanings. Special attention is given to partonymic relations related to different levels of abstraction and professional domains. The research results contribute to the theoretical enrichment of linguistics and practical application in lexicography, education, and translation. Cultural and social aspects reflecting the unique features of the Uzbek language are particularly emphasized.